The wonder years - Dale, Richard; Goldberg, Robert (Wonders of the human body, 2002)
Your journey through the human body continues as you follow the astonishing changes we undergo as we grow from toddler to teen. Witness the amazing role the brain plays in this transformation. Marvel at the development of all the organs we need to survive-lungs, heart, stomach, skin and more. Through state of the art imaging techniques, miniscule inside the body cameras, time-lapse photography, computer morphing, digital animation and more the whole family can see, understand and enjoy the science of this astonishing creation in this programme.